Detection of the White Dwarf Spin of the Long-orbital Period Magnetic Cataclysmic Variable V1082 Sgr - I. J. Lima; G. Tovmassian; C. V. Rodrigues; A. S. Oliveira; G. J. M. Luna; D. A. H. Buckley; K. M. G. Silva; A. C. Mattiuci; D. C. Souza; W. Schlindwein; F. Falkenberg; M. S. Palhares (The Astrophysical Journal)
We report on the discovery of circular polarization modulated with a period of 1.943 ± 0.002 hr in the cataclysmic variable V1082 Sgr. These findings unambiguously reveal the rotation of a magnetic white dwarf and establish its intermediate polar nature. Along with its extraordinary long orbital period ( P _orb ) of 20.8 hr, the spin period ( P _spin ) places this system in an extreme position of the P _spin versus P _orb distribution. The circular polarization phase diagram has a single peak and an amplitude smaller than 1%. These data were used to model the postshock region of the accretion flow on the white dwarf surface using the CYCLOPS code. We obtained a magnetic field in the white dwarf pole of 11 MG and a magnetospheric radius consistent with the coupling region at around 2–3 white dwarf radii. The P _spin / P _orb value and the estimated magnetic field momentum suggest that V1082 Sgr could be out of spin equilibrium or in a spin-up state, possibly in a stream accretion mode.